Pemberdayaan Bank Sampah Gemi Nastiti untuk Meningkatkan Kesejahteraan dan Kualitas Lingkungan di Desa Makamhaji Kecamatan Kartosuro Kabupaten Sukoharjo: Empowerment of Gemi Nastiti Waste Bank to Improve Welfare and Environmental Quality in Makamhaji Village, Kartosuro District, Sukoharjo Regency - Wiwit Rahayu; Darsono Darsono; Sri Marwanti; Minar Ferichani; Umi Barokah; Ernoiz Antriyandarti; Susi Wuri Ani (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
In Sukoharjo Regency, more than 140 tons/day of waste goes to the TPA. One of the efforts to solve the waste problem is by establishing a waste bank, one of which is the